Peran Spiritual Bagi Kesehatan Mental Mahasiswa di Tengah Pandemi Covid-19 - Desti Azania; Naan Naan (HUMANISTIKA : Jurnal Keislaman, 2021)
In this study, it examines the role of spirituality for the mental health of students in the midst of the Covid-19 pandemic. The research subjects were 15 students of Sunan Gunung Djati University with 5 male respondents and 10 female respondents. The data obtained is the result of collecting results using google form with a closed question system. From the results of this study, it can be found that students have a level of anxiety when they are at the beginning of the Covid-19 pandemic, they are threatened with anxiousness to leave the house and interact with other people, but that anxiety is stopped because there are spiritual behaviors experienced by students, one of which is dzikir. , almost all respondents carried out health protocols very well in order to break the chain of the corona virus, even students always thought that the covid-19 pandemic would end soon which prevented mental illness that occurred to students and students always filtered the news first for consumption, of course the news was related to the covid-19 virus. Where this is an important role for spirituality and mental health.